2016
DOI: 10.1002/cbin.10653
|View full text |Cite
|
Sign up to set email alerts
|

Fructose sensitizes Jurkat cells oxidative stress‐induced apoptosis via caspase‐dependent and caspase‐independent mechanisms

Abstract: Whether fructose (FRU), as the sole energy source, confers a metabolic advantage on cancer cells against noxious stimuli is unknown. The aim of this study was to evaluate the effects of low (11 mM), moderate (25 mM), and high (55 mM) FRU concentrations alone or in combination with rotenone (ROT) or doxorubicin (DOX) in Jurkat cells, an acute lymphoblastic leukemia cell model. Glucose (GLU) was used as a control. Using different cell analysis techniques, we demonstrated that FRU was predominantly metabolized vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…This is especially the case when the liver has lower levels of antioxidant protection to cope with the generation of ROS [44], which react with macromolecules including deoxyribonucleic acid (DNA), proteins, and the components of cellular membranes [45]. NO, another factor that is involved in oxidative stress, induces the formation of hydroxyl radicals, which are involved in alcohol-induced liver damage [46].…”
Section: Discussionmentioning
confidence: 99%
“…This is especially the case when the liver has lower levels of antioxidant protection to cope with the generation of ROS [44], which react with macromolecules including deoxyribonucleic acid (DNA), proteins, and the components of cellular membranes [45]. NO, another factor that is involved in oxidative stress, induces the formation of hydroxyl radicals, which are involved in alcohol-induced liver damage [46].…”
Section: Discussionmentioning
confidence: 99%
“…13 Notably, more and more evidences indicated that reactive oxygen species (ROS) were also strongly involved in the response to cancer therapeutics. 14 Thus, stimulation of autophagy by rhArg through depleting arginine and mitochondrial-derived ROS production have been highlighted in the treatment with rhArg for NSCLC.…”
mentioning
confidence: 99%
“…This is especially the case when the liver has lower levels of antioxidant protection to cope with the generation of ROS (Diaz-Aguirre et al. 2016 ). ROS and MDA cause oxidative damage to biological macromolecules including nucleic acids and proteins (Sun et al.…”
Section: Discussionmentioning
confidence: 99%